TANGGAPAN RESPONDEN TERHADAP MEDIA PEMBELAJARAN GAME KANJI TABI - Akmal El-adly; Anisa Arianingsih (Fakultas Ilmu Budaya, Universitas Komputer Indonesia, 2022)
This study aims to determine the responses of respondents to the kanji tabi game learning media. The method used is the ADDIE method (Analysis, Design, Development, Implementation, Evaluation). Making kanji tabi game using Godot engine software. Questionnaires were used as a tool to collect respondents' responses and distributed to 16 11th grade students at MA Alhuda Pameungpeuk. The results of respondents' responses to the kanji tabi game learning media show that kanji tabi is included in the neutral interval and agrees with the criterion value of 572 on the rating scale. The results of these criteria can be concluded that the media for learning the kanji tabi game is quite good and can help beginners learn kanji N5. This media is expected to help students in learning the N5 kanji. Keywords: Japanese language, kanji N5, learning media, godot engine